Color Terms in Mongolian Place Names: A Typological Perspective - Enkhjargal Purev; Oyunsuren Tsend; Purevsuren Bazarjav; Temuulen Khishigsuren (Вопросы ономастики, 2023)
With their implications for human perception and conceptualization of the physical environment, place names have been largely analyzed from a cognitive perspective. This article aims to extend such cross-disciplinary studies by investigating the use of color terms in place names. The authors use a large-scale database of 214,805 toponyms of Mongolia to identify place names that feature color terms, both basic and non-basic, and compare them with previous literature on the toponymy of other countries and languages. Our results can be summed up in three major findings. (1) The most frequently attested color terms in Mongolian toponymy (namely, ‘black,’ ‘white,’ and ‘red’) prove to be identical to the most salient “toponymic colors” in other territories and cultures as can be seen from the analysis of previous research. The phenomenon of similar behavior of color terms in place names across different languages and cultures requires an explanation based on the universal cognitive mechanisms of color perception and development of color terminology. (2) Color terms are more frequently found in the toponymy of desert and steppe areas of Mongolia than in continental climate areas, which can be explained by the topographic properties of these two zones and universal cognitive mechanisms of place naming. Along with that, it was found that all Mongolian place names feature a unified set of color terms regardless of the region and topographic environment. (3) Against the typological background, Mongolian toponyms appear to be culture-specific in that they largely feature animal coat colors, as nomadic lifestyle and stock-raising have always been an essential part of the culture and, in the past, had a major impact on the color terminology of Mongolians. Such onomastic investigation into place names with color terms helps broaden our understanding of the cognitive mechanisms of place naming in different cultures and contributes to the color studies in cognitive sciences.